Pepsin-induced coagulation of casein micelles: Effect of whey proteins and heat treatment. (15th February 2023) - Yang, Mengxiao; Ye, Aiqian; Yang, Zhi; Everett, David W.; Gilbert, Elliot Paul; Singh, Harjinder
Highlights: Whey proteins did not impact the hydrolysis of κ-casein but retarded coagulation. Heat treatment had little impact on hydrolysis and coagulation in WP-free samples. Heat treatment slightly impaired the hydrolysis of WP-containing samples. The coagulation of WP-containing samples changed after heat treatment. Heated WP samples with finer microstructure had higher water holding capacity. Abstract: The effect of whey proteins and heat treatment (90 °C, 5 min) on pepsin-induced hydrolysis of κ-casein, and subsequent coagulation of casein micelles, was investigated at pH 6.3 and 6.0 using reverse-phase HPLC, oscillatory rheology, and confocal laser scanning microscopy. Whey proteins did not affect the hydrolysis of κ-casein but retarded the coagulation process. Heat treatment did not affect the hydrolysis kinetics in whey protein (WP)-free samples, but slightly impaired the hydrolysis rate in WP-containing samples. The coagulation process of WP-free samples was little affected by heat-treatment. However, compared with unheated WP-contained sample at the same pH, the coagulation process of the heated sample was retarded at pH 6.3 but enhanced at pH 6.0. The curd in heated samples with smaller pores had higher water holding capacity. This knowledge provides further understanding on the role of whey proteins and heat treatment on the coagulation mechanisms of milk under gastric conditions.